REPRESENTASI PEREMPUAN DALAM TABLOID WANITA (Studi Kasus Tabloid Nova dan Tabloid Nyata) - Silvia Riskha Fabriar (An-Nida : Jurnal Komunikasi Islam, 2016)
The existence of women's tabloids is expected as a medium to provide new spirit through the presence of articles that empower women's position in both domestic and public areas. However, the reality is reversed. Tabloid presents presentations and ideas that tend to make women's tabloids as a consumptive lifestyle-shaped lifestyle and market a variety of products for women as well as places for women to deal with domestic or household.